Multiple zones surveillance system using RFID - Mohamad Hanif, Noor Hazrin Hany; Daud, Hanita; Yahya, NoorHana; Ibaharin, Mohd Amirul (WSEAS, 2010)
Monitoring and tracking the activities of individuals (or objects) in multiple zones or areas simultaneously is quite a challenging task. It is a very common practice to use observation cameras or to have security personnel to guard the specified areas. However, area surveillances using these common methods may become tedious when the activities to watch out for increases. More cameras as well as manpower are needed to cater for the increment of activities for each zone. On top of that, should anyone (or objects) vacates or trespasses the designated areas, it would take some time to identify them, hence resulting complexity in tracing their whereabouts. To overcome these challenges, we propose a surveillance system for multiple zones using RFID technology. Individuals or objects to be monitored are tagged using RFID tags that hold unique identification. Each zone is allocated with one RFID reader, which will transmit the information of activities of the respective zones to the host computer in the control room. The security personnel in the control room would be able to identify which individual or objects that are out of their designated zones or trespassing to another zone based on the tags that has been detected by the reader. Should the tags are removed without authorization, alarm will be generated. Every activity transactions are recorded in a database for future references or actions. A case study of inmate tracking system is conducted and demonstrated to prove the capability of the proposed method.